Modern strategies for learning a foreign language in training future teachers of the updated school - Kabbassova, Ainagul; Sakenov, Janat (Pedagogy and Psychology, 2021)
Abstract The relevance of teaching a foreign language to future teachers in the context of updating school education puts forward requirements for the choice of teaching strategies. The article deals with the meta-subject aspect of foreign language training of future teachers. To form the readiness of future teachers to use the potential of a foreign language, it is important to understand the basic principles of integrating the content of special disciplines and knowledge of a foreign language. The meta-subject potential of a foreign language allows you to create opportunities for the development of general and special professional competencies. The formation of the competencies necessary to work with the updated content of education is the main task of the courses of the component for the choice of the bachelor’s degree program at pedagogical university. The selection of optimal learning strategies contributes to the implementation of this task. The author examines the features of the use of modern pedagogical technologies and methods in the training of teachers of a new format.